Effects of Brief Acceptance and Cognitive Reappraisal Interventions on Experiential Avoidance in Socially Anxious Individuals: A Preliminary Investigation. Issue 6 (November 2020) - Spencer, Samuel D.; Buchanan, Jeffrey A.; Masuda, Akihiko
The current study compared the effects of 15-min acceptance-based and cognitive reappraisal–based interventions on experiential avoidance (EA) in socially anxious college students who participated in an experimental public speaking task. Participants were randomly assigned to receive one of the two interventions designed to aid in preparation for a 5-min laboratory-based public speaking task. Results indicated that participants receiving the acceptance-based intervention reported significantly lower levels of EA at the post–public speaking task measurement time, indicating that this brief acceptance–based intervention yielded the proposed mechanism of action in the sample used for this study. These findings highlight the importance of process-based accounts of cognitive-behavioral psychotherapy and shed light on the importance of developing interventions for alleviating social anxiety.